2022
DOI: 10.1007/s11145-022-10328-9
|View full text |Cite
|
Sign up to set email alerts
|

Is it the size, the movement, or both? Investigating effects of screen size and text movement on processing, understanding, and motivation when students read informational text

Abstract: This study focused on the potential effects of screen size (smartphone vs. tablet) and text movement (scrolling vs. paging) on integrated understanding of text information, strategic backtracking, and intrinsic reading motivation when Norwegian university students read an informational text on either a smartphone or a tablet by either scrolling or paging. We expected that paging would lead to better integrated understanding of the text and more strategic backtracking than scrolling. Also, we explored whether s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…With respect to page navigation, no difference was found between horizontal paging and vertical scrolling. Although previous research suggested that scrolling could hinder readers’ construction of text structure (Haverkamp et al, 2023), this seems not to be the case when reading on handheld devices. However, it should be noted that only five primary effect sizes in our data set came from studies in which vertical scrolling was used to navigate the texts.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…With respect to page navigation, no difference was found between horizontal paging and vertical scrolling. Although previous research suggested that scrolling could hinder readers’ construction of text structure (Haverkamp et al, 2023), this seems not to be the case when reading on handheld devices. However, it should be noted that only five primary effect sizes in our data set came from studies in which vertical scrolling was used to navigate the texts.…”
Section: Discussionmentioning
confidence: 84%
“…This feature, for example, allows the reader to get physically closer to the text when processing the content more in-depth (Ballenghein et al, 2020). Moreover, the layering of text pages on a handheld device is also more similar to that of pages in printed texts, which supports strategic backtracking to a higher extent than scrolling (Haverkamp et al, 2023).…”
Section: Handheld Devices and The Screen Inferiority Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Gellert and Elbro (2013) concluded that the test was both valid and reliable after correlating it with standardized tests of reading comprehension. Reliability was satisfactory (Cronbach's α = 0.85) in a prior study including Norwegian secondary students (Bråten et al, 2019), and in two studies including Norwegian university students with α = 0.89 in Haverkamp et al (2022) (BA/MA students) and α = 0.83 in Latini et al (2019) (BA students). In the two studies including university students, analyses of correlation showed a statistical significantly relationships between the cloze comprehension test and text integration measures.…”
Section: Text Comprehensionmentioning
confidence: 89%
“…Although the text comprehension test has been demonstrated to have acceptable reliability and validity in several studies (e.g. Gellert and Elbro, 2013;Haverkamp et al, 2022), a cloze test will normally be restricted to measuring comprehension at sentence and passage level (Trace, 2020). Hence, the text comprehension measure could be accompanied by a measure of multiple text or digital text comprehension, potentially measuring the challenges readers often are confronted with in evaluating and integrating information across different sources (Bråten et al, 2018).…”
Section: Limitations and Future Researchmentioning
confidence: 99%